Mysteries of meteors, asteroids, and comets - Labrecque, Ellen (2021)
"What are asteroids, comets, and meteors made of? What can scientists do if an asteroid is headed toward Earth? Learn how astronomers prepare for space objects hitting Earth, from tracking them to building asteroid-hunting telescopes. Budding astronomers will learn all about meteors, asteroids, and comets, including the history of asteroids hitting Earth and the differences between space rocks"--
Smashing into Earth -- Defending planet Earth -- Asteroids -- Meteoroids, meteors, and meteorites -- Comets -- From far away -- What is still a mystery?.
Includes bibliographical references and index.
Ages 8-11
Grades 4-6
Keywords: Asteroids -- Juvenile literature; Meteors -- Juvenile literature; Comets -- Juvenile literature